2015
DOI: 10.1515/cclm-2015-0179
|View full text |Cite
|
Sign up to set email alerts
|

Discriminant indices for distinguishing thalassemia and iron deficiency in patients with microcytic anemia: a meta-analysis

Abstract: Background: More than 40 mathematical indices have been proposed in the hematological literature for discriminating between iron deficiency anemia and thalassemia trait in subjects with microcytic red blood cells (RBCs). None of these discriminant indices is 100% sensitive and specific and also the ranking of the discriminant indices is not consistent. Therefore, we decided to conduct the first meta-analysis of the most frequently used discriminant indices. Methods: An extensive literature search yielded 99 ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
90
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 60 publications
1
90
0
4
Order By: Relevance
“…In meta-analysis study to distinguish individuals with β -TT and IDA, Hoffmann et al (2015) have noted that microscopic smear examinations and CBC are difficult to be performed in rural area since the source and personnel to examine the smear are scarce, and CBC analyzer is expensive and not portable [22]. For example, in rural area where equipment or expertise is scarce, One Tube Osmotic Fragility Test (OTOFT) is a simple test that can be done to examine carriers [23].…”
Section: Discussionmentioning
confidence: 99%
“…In meta-analysis study to distinguish individuals with β -TT and IDA, Hoffmann et al (2015) have noted that microscopic smear examinations and CBC are difficult to be performed in rural area since the source and personnel to examine the smear are scarce, and CBC analyzer is expensive and not portable [22]. For example, in rural area where equipment or expertise is scarce, One Tube Osmotic Fragility Test (OTOFT) is a simple test that can be done to examine carriers [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, its specificity is limited by some other conditions, such as thalassemia and anemia of chronic disease. The ratio of microcytic to hypochromic RBC count may help us to distinguish it from thalassemia [20], and the sTfR index will help to distinguish between IDA and anemia of chronic disease [4]. The study showed that CHr has a strong correlation with hemoglobin, MCV, and MCH, meaning that CHr combined with these conventional parameters appears to be available and reliable in identifying IDA [19].…”
Section: Discussionmentioning
confidence: 99%
“…Several haematological indices are introduced to categorize microcytic anaemia into an iron deficiency anaemia (IDA) or a carrier state of β-thalassemia, such as the Mentzer index (MCV/RBC), Srivastava index (MCH/RBC), Shine & Lal index (MCV [2]*MCH/100) and many other indices [5]. However, the sensitivity and specificity of these indices vary across regions [6]. Although haematological indices can be used to diagnose presumptive β-thalassemia carriers, a recent development shows that Hb analysis, including fractions of HbA2, HbA, or HbF, may confirm or exclude the β-thalassemia carrier state.…”
Section: Introductionmentioning
confidence: 99%